SnS nanoparticles as an artificial solid electrolyte interphase and effective conductive additive in silicon anodes. (10th December 2021) - Zhu, Junchao; Yang, Tao; Fu, Yunhan; Sheng, Bibo; Lin, Rongying
Highlights: High-performance heterostructure Si@SnS anode material is facile prepare. The role of SnS in improving the performance of silicon-based anode materials is clearly explained. Si@SnS displays high discharge performance and excellent cycle stability. In situ XRD has been used to study the lithium storage mechanism of SnS. Abstract: Using a simple hydrothermal method, we developed a Si@SnS anode material with SnS nanoparticles uniformly attached to the surface of silicon nanoparticles. Utilizing the first charge-discharge reaction mechanism of SnS, combined with the artificial solid electrolyte interphase to improve the solid electrolyte interphase stability of silicon-based materials and the introduction of conductive additives to improve the conductive properties of silicon-based materials, the Si@SnS material exhibits very excellent performance when applied to lithium-ion battery anodes. At a current density of 0.5A . g −1, after two cycles, the overall resistance of the Si@SnS material battery is reduced by nearly 55% relative to the resistance of the pure silicon battery. As a half-cell anode material, the first coulombic efficiency of Si@SnS at a current density of 1A . g −1 reached 85%, and after 200 cycles, it provided a reversible capacity of 1790 mAh . g −1 and a capacity retention rate of 74.6%. Graphical abstract: Image, graphical abstract